Value of Cerebroplacental Ratio in Predicting Adverse Perinatal Outcome in Term Pregnancies Complicated by Obesity - Eisenkolb, Gabriel; Karge, Anne; Ortiz, Javier U.; Ostermayer, Eva; Lobmaier, Silvia M.; Kuschel, Bettina; Graupner, Oliver (Geburtshilfe und Frauenheilkunde, 2024)
To evaluate the performance of cerebroplacental ratio (CPR) in predicting composite adverse perinatal outcome (CAPO) in women with obesity compared to non-obese women at term.This is a retrospective cohort study in a single tertiary referral centre over a 3-year period. All singleton pregnancies with CPR measurements ≥ 37 + 0 weeks and estimated fetal weight ≥ 10th centile and attempted vaginal delivery were included and divided into two groups defined by pre-pregnancy body mass index (BMI) </≥ 30 kg/m2. The presence of at least one of the following outcome parameters was defined as CAPO: operative delivery (OD) due to intrapartum fetal compromise (IFC), admission to the neonatal intensive care unit, umbilical cord arterial pH ≤ 7.15, 5 min Apgar < 7. The prognostic performance of CPR MoM was evaluated using receiver operating characteristic (ROC) analysis.The study cohort included 1207 pregnancies, of which 112 were women with a BMI ≥ 30 kg/m2. In obese women, CAPO occurred in 21 cases (18.8%) compared to 247 (22.6%) cases in women with BMI < 30 kg/m2 (p = 0.404). In the entire study cohort, CPR MoM was significantly lower in the CAPO and OD for IFC group. ROC analyses revealed a significant predictive value of low CPR MoM for CAPO in obese women (AUC = 0.64, p = 0.024). Furthermore, CPR was predictive for OD for IFC not only in obese (AUC = 0.72, p = 0.023) but also in non-obese (AUC = 0.61, p = 0.003) women.Low CPR MoM was predictive for CAPO and OD for IFC in obese women without additional risk factors. However, the overall predictive performance of CPR for CAPO in obese women was poor.
Keywords: cerebroplacental ratio; obesity; BMI; adverse perinatal outcome